2015
DOI: 10.3758/s13421-015-0518-2
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of learning in choice reactions: The roles of stimulus type, response mode, and set-level compatibility

Abstract: The Simon effect refers to the advantage of responding to spatially compatible stimuli. This effect can be eliminated or even reversed to favor spatially incompatible stimuli after participants practice a choice-reaction task with spatially incompatible mappings (e.g., pressing left and right keys to stimuli on the right and left, respectively). This transfer of incompatible spatial associations has been observed under conditions in which responses were made manually (e.g., keypresses, moving a joystick). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…A more promising possibility concerns the type of representation of the digit sequences and/or motor patterns. As mentioned in the Introduction, the generalizability found in the present study could be attributed to a representation of the abstract structure of the skill (as opposed to the surface structure; Dominey et al, 1998), or a representation that is effector independent (Boutin et al, 2012;Park & Shea, 2005;Verwey & Clegg, 2005) and does not require a contextual match between the practice and transfer tasks (Yamaguchi et al, 2015).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A more promising possibility concerns the type of representation of the digit sequences and/or motor patterns. As mentioned in the Introduction, the generalizability found in the present study could be attributed to a representation of the abstract structure of the skill (as opposed to the surface structure; Dominey et al, 1998), or a representation that is effector independent (Boutin et al, 2012;Park & Shea, 2005;Verwey & Clegg, 2005) and does not require a contextual match between the practice and transfer tasks (Yamaguchi et al, 2015).…”
Section: Discussionsupporting
confidence: 51%
“…Generalizability could also be explained in terms of the subjects' representation of the digit sequences and/or motor patterns. In particular, compatible with generalizability would be a representation of the abstract structure of the skill (rather than its surface structure; see, e.g., Dominey, Lelekov, Ventre-Dominey, & Jeannerod, 1998), an effector-independent representation (Boutin et al, 2012;Park & Shea, 2005;Verwey & Clegg, 2005), or a representation that does not necessitate a contextual match between the tasks given in practice and transfer (Yamaguchi, Chen, & Proctor, 2015).…”
Section: Present Studymentioning
confidence: 99%
“…This suggests that physical locations and arrows access the same spatial representations, whereas arrow and word stimuli tap overlapping semantic codes. In addition, Yamaguchi, Chen, and Proctor (2015) found similar transfer when a verbal response was used after training on manual incongruent spatial location responses.…”
Section: Introductionmentioning
confidence: 74%
“…For both Simon and Stroop paradigms, pretraining on spatially incompatible response mappings can reduce interference effects. This appears to transfer across stimuli and, to some extent, different modalities of presentation and response (Marini, Iani, Nicoletti, & Rubichi, 2011;Yamaguchi, Chen & Proctor, 2015). Specifically, Procter, Yamaguchi, Zhang, and Vu (2009) found that practicing with incongruent spatial locations and responses abolished the Simon effect.…”
Section: Introductionmentioning
confidence: 95%
“…This has also been shown to account for task settings in which categorical coding appears appropriate (e.g., Yamaguchi & Proctor, 2011). Whether this approach could account for the Simon effect with symbolic stimuli (e.g., spatial words and arrows; Proctor, Yamaguchi, Zhang, & Vu, 2009;Yamaguchi, Chen, & Proctor, 2015) would be an interesting issue to address in future investigations.…”
Section: Discussionmentioning
confidence: 95%